Mass spectrometric studies of 1‐ethyl‐3‐methylimidazolium and 1‐propyl‐2, 3‐dimethylimidazolium bis(trifluoromethyl)‐sulfonylimides. (26th May 2015) - Chilingarov, Norbert S.; Medvedev, Artem A.; Deyko, Grigoriy S.; Kustov, Leonid M.; Chernikova, Elena A.; Glukhov, Lev M.; Markov, Vitaliy Yu.; Ioffe, Il'ya N.; Senyavin, Vladimir M.; Polyakova, Marina V.; Sidorov, Lev N.
Abstract : Rationale: Ionic liquids ([Cat + ][An − ]) were believed to decompose before reaching vaporization temperatures, but recently some of them have been shown to vaporize congruently. Low‐temperature vaporization of ionic substances is an intriguing phenomenon, so the vapor‐phase composition and reactions of ionic liquids deserve more extensive study. Methods: Evaporation of two ionic liquids, [C2 MIM + ][Tf2 N − ] and [C3 MMIM + ][Tf2 N − ], was studied by means of Knudsen effusion mass spectrometry. These liquids were also characterized using matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry, UV/Vis, IR, NMR spectroscopy, and elemental analysis. Results: The vaporization enthalpies of (118 ± 3) and (124 ± 2) kJ·mol −1 were determined for [C2 MIM + ][Tf2 N − ] and [C3 MMIM + ][Tf2 N − ], respectively. The corresponding equations for their saturated vapor pressures are: ln p C 2 MIM + T f 2 N − / Pa = – 14213 ± 325 / T / K + 26.57 ± 1.04, ln p C 3 MMIM + T f 2 N − / Pa = – 14868 ± 221 / T / K + 27.19 ± 0.60 . The MALDI studies (positive and negative ion modes) enabled detection of monomeric [Cat + ] and [An − ] ions, the cluster ions {[Cat + ]2 [An − ]} + and {[Cat + ][An − ]2 } −, and some complex anions {2[An − ]+Na + } −, {2[An − ]+K + } −, {2[An − ]+Cu + } − and {3[An − ]+Ca 2+ } − . Conclusions: Knudsen effusion mass spectrometry proved to be a valuable method to study the thermodynamics of ionic liquids. The saturated vapor pressure and vaporization enthalpy of [C3 MMIM + ][Tf2 N − ] were accurately determined for the first time. MALDI is also capable of providing indirect information on hydrogen bonding. Copyright © 2015 John Wiley & Sons, Ltd.